Association of Autoimmune Thyroid Disease with Anti-GAD Antibody ELISA Test Positivity and Risk for Insulin Deficiency in Slowly Progressive Type 1 Diabetes - Masahito Katahira; Hidetada Ogata; Takahiro Ito; Tsutomu Miwata; Megumi Goto; Shizuka Nakamura; Hiromi Takashima (Journal of Diabetes Research)
The presence of antiglutamic acid decarboxylase antibody (GADA) is required for the diagnosis of slowly progressive type 1 diabetes (SPT1D). We examined the factors influencing GADA determination by radioimmunoassay (GADA-RIA) and by enzyme-linked immunosorbent assay (GADA-ELISA). Sixty patients with SPT1D and 154 patients with type 2 diabetes were examined by both GADA-RIA and GADA-ELISA and for the presence of autoimmune thyroid disease (AITD). We compared the clinical characteristics of these patients based on the positivity or negativity of GADA-RIA and GADA-ELISA, and the existence or nonexistence of AITD. Thirty of 60 (50.0%) GADA-RIA-positive patients were GADA-ELISA negative, whereas none of the 154 GADA-RIA-negative patients were GADA-ELISA positive. Concomitant AITD was significantly less in patients with GADA-RIA and without GADA-ELISA and was significantly more in patients with GADA-RIA and GADA-ELISA. In GADA-RIA-positive patients, there was no significant difference in the GADA-RIA titer among the GADA-ELISA-negative patients with and without AITD, and the GADA-ELISA-positive patients without AITD; whereas the frequency of insulin deficiency was significantly higher in the patients with AITD and/or GADA-ELISA than in those without AITD and GADA-ELISA. Examination of GADA-ELISA and AITD in GADA-RIA-positive patients might be useful in predicting insulin deficiency in these patients.